List of butter factories, cheese factories, condenseries, receiving stations, powdered milk plants, and casein plants (Wisconsin Dept. of Agriculture and Markets, Dairy and Food Division, 1930)
Includes Wisconsin dairy statistics for 1927 and 1929.